AI-POWERED HEALTHCARE. - Yuan Yuan (Beijing Review, 2025)
The article discusses the integration of artificial intelligence (AI) in healthcare at Chizhou Hospital of Traditional Chinese Medicine and the First Affiliated Hospital of the University of Science and Technology of China. AI systems are used for health status identification, diagnosis, and treatment recommendations, aiming to enhance medical services and improve diagnostic efficiency. While AI offers significant benefits, there are challenges related to legal, ethical, safety, and technical aspects that need to be addressed through legislation to ensure accountability, patient safety, and ethical guidelines in AI healthcare applications.